Peer Enhancement of a Brief Motivational Intervention With Mandated College Students - Tevyaw, Tracy O’Leary (2007)
In this pilot study, the authors evaluated whether incorporating a peer in a brief motivational intervention would lead to significant reductions in alcohol use and problems in students mandated to receive treatment after violating campus alcohol policy. Thirty-six participant–peer dyads (66% male) were randomly assigned to receive either two 45-min sessions of an individual motivational intervention (IMI, n = 18) or a peer-enhanced motivational intervention (PMI, n = 18). The IMI included exploration of motivation to change alcohol use, perceived positive and negative effects of drinking, personalized feedback, and goals for changing alcohol consumption and related behaviors. The PMI included all elements of the IMI plus the presence of a supportive peer of the participant during both sessions. Although both groups significantly reduced number of drinking days and heavy drinking days at 1-month follow-up, the magnitude of within-group reductions in alcohol use and problems was 3 times larger on average for the PMI group than for the IMI group, based on effect-size calculations. Peers and participants endorsed high satisfaction ratings on the PMI. Findings indicate the promise of including peers in brief motivational interventions for mandated students.